The Principal's Managerial Strategy in Optimizing Local Wisdom Extracurricular Activities in The Curriculum at SDN 006 Palaran - Maimunah, Isti; Harmawati, Harmawati; Ikhwanul, Muhammad; Suratman, Suratman (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2026)
Education in the current era of globalization is facing serious challenges in the form of moral degradation and the fading of local cultural identity among the younger generation. In response to this, the learning process is required to no longer focus solely on theoretical aspects, but must also provide contextual learning experiences through the integration of character values and local wisdom. This study aims to comprehensively analyze the principal's managerial strategies in optimizing local wisdom-based extracurricular activities to strengthen the educational character and cultural resilience of students at SDN 006 Palaran. This research adopts an interpretive paradigm through a qualitative approach with a descriptive case study design specification executed in a naturalistic manner. The phenomenon of discipline and subject interactions are investigated organically at the focus of the educational institution without any intervention or manipulation of research variables, in order to explore a holistic understanding of the patterns and articulation of established curriculum implementation at the institution. The implementation phase was realized through the internalization of values in extracurricular activities such as the preservation of regional dances and visits to cultural sites supported by the school culture and optimal utilization of resources. Meanwhile, the evaluation phase was carried out through authentic assessments of changes in student behavior that functioned as a tool for reflection and quality control through a continuous improvement approach. Research findings indicate that a non-centralized management strategy has proven effective in optimizing local school potential independently. This study emphasizes that an innovative approach through optimizing extracurricular activities focuses not only on implementation but also on the principal's strategy in developing a curriculum that supports a supportive learning environment.